Moderate intensity continuous training reverses the detrimental effects of ovariectomy on RyR1 phosphorylation in rat skeletal muscle. (5th February 2019) - Zügel, M.; Wehrstein, F.; Qiu, S.; Diel, P.; Steinacker, J.M.; Schumann, U.
Abstract: High 17β-Estradiol (E2) concentrations in isolated ventricular myocytes as well as a lack of ovarian hormones in cardiac muscle of ovariectomized (OVX) rodents has been shown to lead to arrhythmogenic effects by inducing post-translational modifications, including phosphorylation of the sarcoplasmic reticulum (SR) Ca 2+ release channel ryanodine receptor-2 (RyR2). The effects of estrogens on the phosphorylation status of the RyR1 in skeletal muscle have not been investigated before. Furthermore, while high intensity exercise has been shown to increase RyR phosphorylation, there is no data on the effects of moderate intensity continuous training (MICT). The aims of the study were to investigate the effects of a 3-day treatment with low (1 nM, moderate (5 nM) and high (10 nM, 100 nM) E2 concentrations on RyR1 mRNA and protein expression and phosphorylation status (pRyRSer 2844 ) in cultured C2C12 myotubes and to study the effects of OVX on RyR1 expression and phosphorylation in rat skeletal muscle in combination with 3 weeks of MICT. Treatment with low, physiological E2 concentrations reduced dihydropyridine receptor (DHPR) and RyR1 mRNA content in C2C12 myotubes compared to untreated control cells, whereas RyR1 protein phosphorylation (pRyRSer 2844 ) was significantly increased after treatment with high, non-physiological E2 concentrations (p ≤ 0.05). RyR1 protein content (p ≤ 0.05) and pRyRSer 2844 (p ≤ 0.05) were significantly elevated in skeletal muscle of OVX vs. sham-operated rats. Importantly, pRyRSer 2844 levels were similar to sham-operated controls in OVX rats after MICT (OVX vs. OVX + MICT, p ≤ 0.05). Our results indicate, that one of the actions of estrogens is to alter skeletal muscle Ca 2+ homeostasis by modulating the expression and phosphorylation of the RyR1 in skeletal muscle. Notably, regular MICT was able to counteract RyR1 phosphorylation in skeletal muscle of OVX rats. Highlights: High (non-physiological) 17β-Estradiol (E2) increases RyR1 Ser2844 phosphorylation in C2C12 cells. Ovariectomy (OVX) increases RyR1 Ser2844 phosphorylation in female rats. Moderate intensity training reverses the increased RyR1 phosphorylation in OVX rats.